Internalisasi Nilai-Nilai Islam dalam Bimbingan Klasikal untuk Mengembangkan Karakter Santri - Laili Budiyono, Alief; Mulya Pratama, Aji (Fakultas Ilmu Tarbiyah dan Keguruan, Institut Agama Islam Bakti Negara Tegal, 2024)
Low morals, ethics and discipline are important to develop among students. Thus, efforts are needed to develop the character of the students, of course with an approach that is in accordance with the culture of the students, which is closely related to Islamic values. This research uses a literature review method which aims to internalize Islamic values ??in classical guidance services to develop the character of students. The results of this research show that Islamic values ??can be integrated into classical guidance services to develop the character of students.